ECONOMIC FEASIBILITY ANALYSIS OF A FOREST-LIVESTOCK INTEGRATION SYSTEM IN ALTA FLORESTA, MATO GROSSO STATE, BRAZIL - Ansolin, Roni Djeison; Timofeiczyk Junior, Romano; Kamoi, Mariana Takahashi; Michetti, Miquéias; dos Reis, Julio Cesar; Garzel Leodoro da Silva, João Carlos (Floresta, 2022)
<span style="line-height: 107%; font-family: ’Times New Roman’,serif; font-size: 9pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This study investigates the economic feasibility of a livestock-forest integration system between Nellore cattle and teak species implemented in Fazenda Bacaeri, in the municipality of Alta Floresta, Mato Grosso state, Brazil. The economic analysis was based on the dataset provided by the Embrapa Agrossilvipastoril and used to elaborate a cash flow, as well as on the following selected criteria, Net Present Value, Internal Rate of Return, and Profitability Index, for a Minimum Attractive Rate of 4.15% annually. The risk analysis was also carried out using the Monte Carlo probabilistic method, considering seven variables, such as the clearcut and thinning wood price, lean cattle selling price, animal acquisition and forest harvesting costs, thinning and clearcutting yield. The calculated analyzed economic indexes are as follows R 4,083,307.77 NPV, 6.48% IRR and 21.36% PI, which indicates the economic feasibility of the studied integration system. The risk analysis shows that this is a low-risk project since the probability of NPV being negative was calculated as 14.4%. However, no matter how efficient the risk prediction tools are, producers must have technical assistance from trained professionals to adequately interpret and mitigate the risks. The studied forest-livestock integration system is economically feasible and low risk.